New Technologies for Educational Practice. An analysis of the teaching practices concerning the use of Web 2.0 tools in today’s school - De Piano, Angela (Formazione & insegnamento, 2015)
The main objective of this research is to analyze the teaching practices concerning the use of Web 2.0 educational technologies. The purpose of this is to know the critical situations that prevent these practices or make them ineffective. Web 2.0 tools support communication and knowledge sharing, and can optimize the learning process. Blogs, wikis and collaborative websites, can allow the creation of Student-Centered Virtual Learning Environments, highly interactive, flexible and open source. This paper wants to analyze the didactic use of the new web technologies: what is the relationship between teachers and these tools? Internet evolution has caused changes in teaching practices? It has been observed, through the use of semi-structured interviews, the employment of web tools by teachers in secondary schools, by finding at the same time solutions for the problems that still exist.